Commodifying femininity: the on-line offering of breast augmentation to New Zealand women. Issue 6 (17th August 2020) - Hopner, Veronica; Chamberlain, Kerry
ABSTRACT: The internet is a knowledge technology and market place, ingrained in everyday social life, which provides an avenue to examine social and gendered relationships. This paper examines a particular gendered arrangement, how breast augmentation is offered to women on internet websites. Breast augmentation is rapidly becoming the most popular cosmetic surgery for Western women. We identified and analysed the content of 20 New Zealand websites offering breast augmentation surgery. Analysis documented two major issues that dominated website presentations. The first positioned breast augmentation as a solution to a deficient breast. Reworking the breast allows possibilities for women to construct revised subjectivities, within socially constrained and gendered norms, dominated by idealized female forms. The second positioned breast augmentation as an elective choice of neoliberal consumerism, constrained by gendered expertise, and a lack of information about the risks and complications of this surgery. We reveal how cosmetic surgery websites selling breast augmentation are complex medicalized sites, raising important issues for further research.